Acúmulo e composição química da forragem em consórcio de quatro espécies sob manejos de colheita e adubação em segunda safra - Matos, Betania Florencio de (2023)
The use of forage mixtures during the off-season in Crop-Livestock Integration (CLI) fields can improve forage production and guarantee straw production for no-till systems. Our objective was to study the effect of different harvest managements with or without topdressing fertilization that affect the accumulation and chemical composition of the forage and the straw production of the mixed of four plants: [Urochloa ruziziensis (R. Germ. & C. M. Evrard), pigeon bean (Cajans cajan L. Millsp), sunflower (Helianthus annuus L.) and buckwheat (Fagopyrum esculentum Moench)], for define the best management method to increment the forage and straw production of this consortium in the second crop. The experimental design was in randomized complete block in a split-plot arrangement with three replications. The treatments were four harvest managements (plot): Intense (3 cuts), Moderate (2 cuts), Light (1 cut) and Straw (no cuts); and two fertilization managements (subplots): 0 or 25 kg ha-1 of nitrogen and potassium. At each harvest, samples were taken to quantify forage accumulation (FA), grass morphological composition, neutral detergent insoluble fiber (DIF), acid detergent insoluble fiber (ADF), crude protein (CP) and mineral matter (MM) of the forage of each plant and the consortium of both. Measurements of leaf area index and intercropping light interception were previously performed before each harvest. There was no effect of fertilization on AF, straw and forage chemical composition in the quadruple mixtures. AF was affected by the year × harvest management interaction. Moderate management had the highest AF in year 1 (7,440 kg DM ha-1 year-1 ) compared to Intense and Moderate (mean of 5,000 kg DM ha-1 year-1 ). In year 2, the highest accumulation occurred in Light management (8,900 kg DM ha-1 year-1 ). Intense presented higher CP concentration in the forage mass (200 g kg-1 ) while Moderate and Light had lower values (100 g kg-1 and 70 g kg-1 , respectively). Light Management had NDF (mean of 635 g kg-1 ) and ADF (mean of 370 g kg-1 ) values higher than Moderate and Intense (mean of 500 g kg-1 and 280 g kg-1 , respectively) . For the straw production, there was an interaction year × management, in which Intense, Moderate and Light had values below the recommended minimum (4,000 kg DM ha-1 ) for no-tillage and management without harvest reached an average of 9,000 kg MS ha-1 . Intense presented lower total forage accumulation when compared to Moderate and Light, however, it presented a forage with better chemical composition, proving to be a management with potential to manage forage mixtures in second crop. The topdressing application of 25 kg ha-1 of N and K does not influence the chemical composition and forage accumulation in the consortium. The Intense, Moderate and Light harvesting managements did not reach the adequate amount of residual forage (straw) for soil cover in no-tillage, requiring an adjustment of the regrowth period with these managements.